2013
DOI: 10.1038/ismej.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of non-ribosomal peptide synthetases and polyketide synthases from the microbiomes of Australian marine sponges

Abstract: The biosynthesis of non-ribosomal peptide and polyketide natural products is facilitated by multimodular enzymes that contain domains responsible for the sequential condensation of amino and carboxylic subunits. These conserved domains provide molecular targets for the discovery of natural products from microbial metagenomes. This study demonstrates the application of tagencoded FLX amplicon pyrosequencing (TEFAP) targeting non-ribosomal peptide synthetase (NRPS) and polyketide synthase (PKS) genes as a method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 54 publications
0
34
1
Order By: Relevance
“…The use of amplicon sequencing to profile soil microbiomes is an attractive approach for assessing the biosynthetic potential of diverse microbiomes to a depth that is still inaccessible via shotgun sequencing. Previously, investigation of natural product biodiversity using amplicon sequencing had only been applied to a small number of marine and terrestrial environments (21)(22)(23)(24)(25). Our study of nearly 100 unique soil samples builds on these earlier small-scale studies to provide a more detailed picture of the distribution of secondary metabolite gene clusters throughout soil microbiomes.…”
Section: Predicting the Distribution Of Gene Clusters That Are Evolutmentioning
confidence: 99%
“…The use of amplicon sequencing to profile soil microbiomes is an attractive approach for assessing the biosynthetic potential of diverse microbiomes to a depth that is still inaccessible via shotgun sequencing. Previously, investigation of natural product biodiversity using amplicon sequencing had only been applied to a small number of marine and terrestrial environments (21)(22)(23)(24)(25). Our study of nearly 100 unique soil samples builds on these earlier small-scale studies to provide a more detailed picture of the distribution of secondary metabolite gene clusters throughout soil microbiomes.…”
Section: Predicting the Distribution Of Gene Clusters That Are Evolutmentioning
confidence: 99%
“…NGS can be very useful in sequence-based approach as it has been demonstrated recently by deep sequencing of amplicons obtained using degenerate primers and eDNA or library as a template. This strategy uncovered more than 50% of the unique PKS and NRPS domains that are accessible from metagenome (Reddy et al 2012;Woodhouse et al 2013).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Pyrosequencing of ketosynthase and condensation domains from marine sponge metagenomes uncovered hundreds of previously unknown sequences, including several clades that had not been previously observed by extensive Sanger sequencing of these sponge metagenomes. (23) Furthermore, a head-to-head comparison of shotgun sequencing of the same samples demonstrated that PCR-based approaches were often 10 to 100 times more sensitive in identifying unique sequences from a metagenome of interest. (23) Even greater biosynthetic biodiversity was observed in desert soil microbiomes, where 1,000s of unique adenylation domain sequences were detected with only a fraction of them shared among distinct microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…(23) Furthermore, a head-to-head comparison of shotgun sequencing of the same samples demonstrated that PCR-based approaches were often 10 to 100 times more sensitive in identifying unique sequences from a metagenome of interest. (23) Even greater biosynthetic biodiversity was observed in desert soil microbiomes, where 1,000s of unique adenylation domain sequences were detected with only a fraction of them shared among distinct microbiomes. A similar pattern was observed for amplicons derived from Type I (ketosynthase) and Type II (ketosynthase alpha) polyketide biosynthesis, suggesting that soil metagenomes are likely to be a rich source of novel bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%